2019
DOI: 10.1103/physrevlett.122.113602
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Semiconductor Source of Entangled Photons Which Simultaneously Has High Fidelity, Efficiency, and Indistinguishability

Abstract: An outstanding goal in quantum optics and scalable photonic quantum technology is to develop a source that each time emits one and only one entangled photon pair with simultaneously high entanglement fidelity, extraction efficiency, and photon indistinguishability. By coherent two-photon excitation of a single InGaAs quantum dot coupled to a circular Bragg grating bullseye cavity with broadband high Purcell factor up to 11.3, we generate entangled photon pairs with a state fidelity of 0.90(1), pair generation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
176
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 276 publications
(181 citation statements)
references
References 66 publications
5
176
0
Order By: Relevance
“…The spectral resonance of the bullseye cavity is strongly sensitive to the radius of the central disk and the grating period. It was previously shown that a 1-nm change of the central disk radius (grating period) causes a 1.14 nm (0.25 nm) shift of the cavity mode 46 . Thus, a 1% ellipticity, which is 23 times smaller than that of our elliptical micropillar, is sufficient to induce a suitable cavity mode splitting.…”
Section: Elliptical Bragg Gratingmentioning
confidence: 99%
“…The spectral resonance of the bullseye cavity is strongly sensitive to the radius of the central disk and the grating period. It was previously shown that a 1-nm change of the central disk radius (grating period) causes a 1.14 nm (0.25 nm) shift of the cavity mode 46 . Thus, a 1% ellipticity, which is 23 times smaller than that of our elliptical micropillar, is sufficient to induce a suitable cavity mode splitting.…”
Section: Elliptical Bragg Gratingmentioning
confidence: 99%
“…the Sirius, within currently available technologies. With a single photon source of better purity [34][35][36] , one can tolerate even feebler starlight and shorten the data accumulation time significantly (see Sec. V of Supplemental Material).…”
Section:  mentioning
confidence: 99%
“…To date, these systems are constrained to cryogenic conditions where interactions with the solid-state environment, in particular the thermal bath of lattice phonons, are adequately suppressed. Even at very low temperatures, only a few systems, such as III-V quantum dots (QDs) [8][9][10], color centers in solids [11][12][13] as well as single molecules [14], have shown FT limited spectral lines. Here we report a solid-state SPE in a two-dimensional (2D) material -hexagonal boron nitride (hBN) -that exhibits FT limited lines at room temperature under resonant excitation (see figure 1(d)).…”
mentioning
confidence: 99%